Constructing Islamic secondary school curricula and textbooks for natural science: an integration framework based on the Ūlū Al-Albāb Model - Hassan, Nur Jannah (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
The annals of the Islamic, modern and post-modern eras are witnesses to how science and technology have impacted humanity. Reacting against the inauspicious effects of modern and post-modern tendencies, is the distinct global phenomenon of Islamic schools offering “integrated education”. But what constitutes as integration? Analyses of various curricula, syllabi and textbooks of natural science used by several Islamic secondary schools in Malaysia, Indonesia, Brunei, Singapore, Southern Thailand, Mindanao and Ontario show very little integration if any. This article puts forward an integration framework towards the construction of Islamic secondary school curricula and textbooks of natural science, based on the Qur’ānic notion of “ūlū al-albāb” with Ghazālian discourse of the qalb where certain conventional aspects of natural science undergo holistic reposition, reinterpretation and reorientation from the Qur’ānic worldview. The framework is constructed on the three-level relationships man has – with God, with humanity and with the cosmos. *******************************************************